Antimicrobial resistance pattern and genetic correlation in Enterococcus faecium isolated from healthy volunteers. (March 2016) - Asadian, M.; Sadeghi, J.; Rastegar Lari, A.; Razavi, Sh.; Hasannejad Bibalan, M.; Talebi, M.
Abstract: Enterococci are known as a cause of nosocomial infections and this aptitude is intensified by the growth of antibiotic resistance. In the present study, Enterococcus faecium isolates from healthy volunteers were considered to determine the antibiotic resistance profiles and genetic correlation. A total 91 normal flora isolates of enterococci were included in this study. Identification of Enterococcus genus and species were done by biochemical and PCR methods, respectively. Sensitivity for 10 antibiotics was determined and genetic relatedness of all isolates was assessed using Repetitive Element Palindromic PCR (REP-PCR) followed by Pulse Field Gel Electrophoresis (PFGE) on the representative patterns. None of the isolates were resistant to teicoplanin, vancomycin, quinupristin-dalfopristin, linezolid, chloramphenicol, ampicillin and high-level gentamicin. On the other hand, the resistance rate was detected in 30.7%, 23%, and 3.29% of isolates for erythromycin, tetracycline and ciprofloxacin, respectively. The results of PFGE showed 19 (61.5% of our isolates) common types (CT) and 35 (38.5%) single types (ST) amongst the isolates. This is the first study to describe antibiotic resistance pattern and genetic relationship among normal flora enterococci in Iran. This study showed no prevalence of Vancomycin Resistant Enterococci (VRE) and high degrees of diversity among normal flora isolates by genotyping using PFGE.